Diagnosis as a strategy for recognizing the presense of disabilities at The National School of Social Work - Lázaro Jiménez, Elía; Silva Montealegre, Tomas (Trabajo Social UNAM, 2016)
Referring to disabilities entails knowing the social model of disability, a model which permits describing the dynamics of disabilities from the social, not the medical, point of view, as was the costume at the beginning of the XX century. This viewpoint sees the causes of disabilities not as religious or scientific, but as social: individual limitations are not the roots of the problem, but rather the limitations of society in providing the appropriate services and thus assuring that the needs of persons with disabilities are taken into account within social organization. Given the situation, the school scenario is a topic which proves important in the matter of disabilities, since this space, besides consolidating the processes of teaching-learning, consolidates the structures of social relations among people. Thus, school-disability becomes a dichotomy in which the socio-educational processes are referenced with the person with a disability. Therefore the present article shows a strategy used by the Comité de Atención a las Personas con Discapacidad de la Universidad Nacional Autónoma de México (Committee for the Attention of Persons with Disabilities of the National Autonomous University of Mexico) CAD-UNAM, in the National School of Social Work, which allowed for recognizing for the first time the presence of persons with disabilities, besides setting the bases for the construction of an Inclusive School and University. A strategy based on the construction of a diagnosis, which permitted discerning the nature and magnitude of the needs, in this case permitted revealing the reality of the presence of persons with disabilities at the National School of Social Work. In this way, in order to approach the subject of disabilities, as well as the persons with disabilities within the school, it is transcendental to participate in a dynamic dialogue which answers the following: What is disability? Who are persons with disabilities? How can I help persons with disabilities? Can persons with disabilities work and/or study at the university?